Opportunities for the treatment of atherosclerosis: Selectins - Nong Li; Chao Pi; Siying Zhu; Xiumei Li; Liu Wang; Peng Shi; Ying Zuo; Wenwu Zheng; Jun Jiang; Yan Yang; Qiong Zhang; Lei Tao; et al. (Pharmacological Research)
Despite the widespread availability of selectins for tumor therapy, their contribution to atherosclerosis has long been under-emphasized due to their “cofactor’s” status and technological limitations. However, advances in immunohistology, glycomics, and related technologies require us to reassess their relationship. Thus, this review identifies pivotal translational opportunities from the intricate mechanisms and explores the clinical promise of selectins in the diagnosis and treatment of atherosclerosis based on the latest clinical research. This review provides insights into selectin-specific tracers and inhibitors, providing lessons for more precise diagnosis and treatment of patients with atherosclerosis.